2016
DOI: 10.18632/oncotarget.13907
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor microenvironment in therapeutic resistance

Abstract: Cancer cells undergo unlimited progression and survival owing to activation of oncogenes. However, support of the tumor microenvironment is essential to the formation of clinically relevant tumors. Recent evidence indicates that the tumor microenvironment is a critical regulator of immune escape, progression, and distant metastasis of cancer. Moreover, the tumor microenvironment is known to be involved in acquired resistance of tumors to various therapies. Despite significant advances in chemotherapy and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
159
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(169 citation statements)
references
References 130 publications
(131 reference statements)
0
159
0
1
Order By: Relevance
“…1 and 2). The TME is a supportive and receptive tissue microenvironment undergoing a series of molecular and cellular changes to form metastatic-designated sites, or the fertile soil in preparation for metastatic tumor cell seed colonization, thus supporting tumor settlement in distant organs and promoting tumor metastasis (6)(7)(8). As the most common immune cells in the TME, TAMs infiltrate the TME in OC in large numbers and play an important role in the formation of the OC TME and education of OC cells to develop to become more malignant by secreting various factors, such as IL-6 and IDO (16,18,19,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and 2). The TME is a supportive and receptive tissue microenvironment undergoing a series of molecular and cellular changes to form metastatic-designated sites, or the fertile soil in preparation for metastatic tumor cell seed colonization, thus supporting tumor settlement in distant organs and promoting tumor metastasis (6)(7)(8). As the most common immune cells in the TME, TAMs infiltrate the TME in OC in large numbers and play an important role in the formation of the OC TME and education of OC cells to develop to become more malignant by secreting various factors, such as IL-6 and IDO (16,18,19,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Although cancer cells unlimitedly proliferate and survive, a tumor microenvironment (TME) is required for the formation and growth of clinically relevant tumors (6). The TME, comprising mesenchymal stem cells, cancer-associated fibroblasts (CAFs), myeloid cells, mesothelial cells and factors released by these cells, contributes to tumor growth, immune escape, distant metastasis and chemoresistance of cancer (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many studies are evaluating the potential of miRNA for achieving a better therapeutic outcomes (Bertoli, Cava, & Castiglioni, ). Pathways such as EMT pathway, MMP/MMP2 pathway and wnt/β‐catenine are proposed to induce therapeutic resistance in cancer (Son et al, ). Interestingly, molecular studies have shown that altered miRNA expression can play a major role in the activation of drug resistance pathways (Hu et al, ).…”
Section: Resistance To Treatment (Radio‐ and Chemoresistance)mentioning
confidence: 99%
“…Immune evasion is intrinsic to the development of cancer and is also a mechanism that cancer cells utilize to avoid chemotherapeutic killing and propagate relapse (Hanahan and Weinberg, 2011; Son et al, 2017). Different mechanisms of immune evasion have been described in detail for solid tumors.…”
Section: Introductionmentioning
confidence: 99%